Developing the Skills and Techniques for the Production of Instructional Materials by Teacher Trainees at Gambaga College of Education - Issah, Mohammed Seini; Alhassan, Hamza; Ibrahim , Fatimatu Hajia (Papanda Publishier, 2024)
The study sought to analyze the skills and techniques acquired by teacher trainees, in art related to producing IMs during teaching practice at Gambaga College of Education (GACE). The role of Instructional Materials is to glue information into learners' minds, as what is seen is understood more than what is heard. Active participation stimulates and motivates learning. The presence of well-prepared IMs in the learning environment creates room for learners to interact or explore with it and that increases the quality of knowledge acquired and broadens the horizon of mastery of knowledge. The study adopted action research and descriptive and experimental methodologies to study the skills and techniques as well as materials adopted for the production of IMs by teacher trainees at GACE. The study found that teacher trainees exhibited poor skills and techniques in the production of IMs. They also adopted materials that can easily be destroyed and in addition, limit pupils' interaction in the lesson. This, therefore, does not motivate pupils to learn.